Islamic Revivalism and Muslim Consumer Ethics - Kamaludeen Mohamed Nasir (2023)
Although scholars have examined the link between religiosity and consumer ethics, the idea of Muslim consumer ethics has not received much traction within academia. The idea of Muslim consumer ethics is a manifestation of religious revivalism. Yet, its discussion must consider the critical roles played by Muslim youth and their consumption of new media because the latter has a profound effect on shaping and directing popular Muslim youth cultures. Muslim consumer ethics encompass the moral and humanistic dimension of living in a globalized world as an extension of an individual’s religious practice. This phenomenon of ethical consumption has also been commoditized in a lucrative halal industry that fosters a Muslim identity market.